Micro‐CT analysis of danger zone thickness in the mesiobuccal roots of maxillary first molars. (2nd November 2018) - Ordinola‐Zapata, R.; Martins, J. N. R.; Versiani, M. A.; Bramante, C. M.
Abstract: Aim: To evaluate dentine thickness from both distal ('danger zone') and mesial ('safety zone') aspects of the MB1 and MB2 canals of maxillary first molars at the furcation level using micro‐CT imaging. Methodology: One hundred maxillary first molars with two canals in the MB root were selected from a Brazilian subpopulation and scanned at a resolution of 19.6 μm in a micro‐CT device. From each specimen, two axial cross‐sectioned images were selected at 2 and 3 mm apical to the furcation level of the MB root and evaluated for the smallest dentinal thickness. Measurements were made from the outer perimeter of the MB1 and MB2 canals towards the external root surface from both distal (danger zone) and mesial (safety zone) aspects of the root. The influence of an isthmus was also considered in the analysis, and samples were classified according to the presence or absence of an isthmus in the axial sections. Non‐parametric Wilcoxon signed‐rank tests were used to compare dentinal thickness between MB1 and MB2 canals with a significant level set at 5%. Colour‐coded 3D models of dentine thickness throughout the MB root were created and evaluated qualitatively. Results: At both levels, median dentine thickness of the MB2 canal was significantly lower in both distal and mesial aspects of the root in comparison with the MB1 canal ( P < 0.01). The presence of an isthmus was not a variable that influenced dentinal thickness. Colour‐coded models indicated that dentine thickness was dependent on the cross‐sectional shape of the MB root. At least 50% of the sample had <1 mm of dentine thickness at the danger zone of the MB2 canal. Conclusions: Danger zones in the MB roots of maxillary first molars were not symmetrical. MB2 canals had less dentine thickness on both aspects of the root compared to the MB1 canal.